(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Discrete trial teaching (DTT) is a procedure widely used for the treatment of individuals with disabilities. Due to its complexity, staff training strategies has been under investigation. Self-instructional manuals are effectual and cost-effective methods to teach DTT. The present work evaluated the effects of using a self-instructional manual (adapted and translated into Brazilian Portuguese) as a training method for the implementation of DTT. Performances of four undergraduate students applying DTT to experimenters role playing children in three tasks (identity matching, pointing to named items, and imitating actions) were evaluated before and after studying the material. The effects of studying the manual were statistically significant over the performances of the participants, although the increase in accuracy was heterogeneous across tasks. Data analysis by behavioral components revealed varied effects over specific skills. These results replicate previous research and indicate that the use of the Brazilian version of the manual is feasible.